UPAYA MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA - Fatimah, Fety; Nani Mediatati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In accordance with the research problem that has been formulated, the aim of this research is to find out how much interest in learning mathematics in class IV students at SD Negeri Kalicacing 02 Salatiga has increased after implementing the TGT type cooperative learning model. The hypothesis in this research is